时量补语 (SHÍ LIÀNG BǓYǓ) –THE USE OF TIME WORDS IN CHINESE - Radjabova Madinabonu Raimovna (Journals Park Publishing, 2023)
In this article, 补 语(bǔyǔ), which is often used in the Chinese language and adds additional meaning to the sentence, belongs to the group of grammatical units called 时量补语 (Shí liàng bǔyǔ), i.e. complements in Uzbek and English. That is, the use of the time complement is indicated. The rules for the use of tenses are explained in a broad and simple way for Uzbeks learning Chinese and for representatives of other languages.
Keywords: 时量补语 (Shí liàng bǔyǔ) tense, grammatical form, complement, adjective, verb, possessive, pronoun, proper noun, 离合动词.